Hospital strain colonization by Staphylococcus epidermidis - D. Blum-Menezes; O.J. Bratfich; M.C. Padoveze; M.L. Moretti (Brazilian Journal of Medical and Biological Research, 2009)
The skin and mucous membranes of healthy subjects are colonized by strains of Staphylococcus epidermidis showing a high diversity of genomic DNA polymorphisms. Prolonged hospitalization and the use of invasive procedures promote changes in the microbiota with subsequent colonization by hospital strains. We report here a patient with prolonged hospitalization due to chronic pancreatitis who was treated with multiple antibiotics, invasive procedures and abdominal surgery. We studied the dynamics of skin colonization by S. epidermidis leading to the development of catheter-related infections and compared the genotypic profile of clinical and microbiota strains by pulsed field gel electrophoresis. During hospitalization, the normal S. epidermidis skin microbiota exhibiting a polymorphic genomic DNA profile was replaced with a hospital-acquired biofilm-producer S. epidermidis strain that subsequently caused repetitive catheter-related infections.